Genetic and Functional Diversity of Pseudomonas aeruginosa in Patients With Chronic Obstructive Pulmonary Disease - Zhao, Kelei; Huang, Ting; Lin, Jiafu; Yan, Chaochao; Du, Lianming; Song, Tao; Li, Jing; Guo, Yidong; Chu, Yiwen; Deng, Junfeng; Wang, Xinrong; Liu, Chaolan; et al. (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa is the most relevant pathogen to the severe exacerbations of patients with chronic obstructive pulmonary disease (COPD). However, the genetic and functional characteristics of P. aeruginosa isolates from COPD airways still remain less understood. In this study, the genetic, phylogenetic, phenotypic, and transcriptional features of P. aeruginosa isolates from COPD sputa were comprehensively explored by susceptibility testing, comparative-genomic analysis, phylogenetic analysis, phenotypic profiling, and comparative-transcriptomic analysis. We found that P. aeruginosa was prevalent in elder COPD patients and highly resisted to many commonly used antibiotics. P. aeruginosa COPD isolates harbored a substantial number of variant sites that might influence the primary metabolism and substance transport system. These isolates were discretely distributed in the phylogenetic tree and clustered with internationally collected P. aeruginosa in two major groups, and could be classified into three groups according to their differences in virulence-related phenotypes. Furthermore, the transcriptional patterns of COPD isolates could be classified into PAO1-like group with reduced protein secretion and motility and PAO1-distinct group with decreased substance transport but enhanced primary metabolism. In conclusion, this study demonstrates that P. aeruginosa isolates from COPD patients have abundant genetic and phenotypic diversity, and provides an important reference for further exploring the survival strategy of P. aeruginosa in COPD airways and the development of anti-pseudomonal therapy.